Acceleration waves in non-ideal magnetogasdynamics - Singh R.; Singh L.P.; Ram S.D. (My University, 2025)
The problem of propagation of acceleration waves in an unsteady inviscid non-ideal gas under the influence of magnetic field is investigated. The characteristic solution to the problem in the neighbourhood of leading characteristics has been determined. An evolution equation governing the behaviour of acceleration waves has been derived. It is shown that a linear solution in the characteristic plane exhibits non-linear behaviour in physical plane. The effect of magnetic field on the formation of shock in non-ideal gas flow with planar and cylindrical symmetry is analysed. It is noticed that all compressive waves terminate into a shock wave. Further, we also compare/contrast the nature of solution in ideal and non-ideal magnetogasdynamic regime. © 2013 Production and hosting by Elsevier B.V. on behalf of Ain Shams University.